A computer-aided continuous assessment system - B. C.H. Turton (Association for Learning Technology, 1996)
Universities within the United Kingdom have had to cope with a massive expansion in undergraduate student numbers over the last five years (Committee of Scottish University Principals, 1993; CVCP Briefing Note, 1994). In addition, there has been a move towards modularization and a closer monitoring of a student's progress throughout the year. Since the price/performance ratio of computer systems has continued to improve, Computer- Assisted Learning (CAL) has become an attractive option. (Fry, 1990; Benford et al, 1994; Laurillard et al, 1994). To this end, the Universities Funding Council (UFQ has funded the Teaching and Learning Technology Programme (TLTP). However universities also have a duty to assess as well as to teach. This paper describes a Computer-Aided Assessment (CAA) system capable of assisting in grading students and providing feedback. In this particular case, a continuously assessed course (Low-Level Languages) of over 100 students is considered. Typically, three man-days are required to mark one assessed piece of coursework from the students in this class. Any feedback on how the questions were dealt with by the student are of necessity brief. Most of the feedback is provided in a tutorial session that covers the pitfalls encountered by the majority of the students.